2016
DOI: 10.3389/fmicb.2016.01179
|View full text |Cite
|
Sign up to set email alerts
|

Solidago canadensis L. Essential Oil Vapor Effectively Inhibits Botrytis cinerea Growth and Preserves Postharvest Quality of Strawberry as a Food Model System

Abstract: This study investigated the anti-fungal properties of Solidago canadensis L. essential oil (SCLEO) against Botrytis cinerea in vitro, and its ability to control gray mold and maintain quality in strawberry fruits. SCLEO exhibited dose-dependent antifungal activity against B. cinerea and profoundly altered mycelial morphology, cellular ultrastructure, and membrane permeability as evaluated by scanning electron microscopy, transmission electron microscopy, and fluorescence microscopy. SCLEO vapor at 0.1 mL/L mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 51 publications
2
40
0
Order By: Relevance
“…Our observation clearly indicated that carvacrol and eugenol fumigation induced the activities of POD and PAL at a few points of incubation. The activities of POD and PAL in peaches exposed to the two EOs observed in this study were consistent with the previous report of Cindi et al (2016) and Liu et al (2016). CHI and b-1,3-glucase decompose chitin and b-1,3-glucan in the cell wall of pathogenic bacteria with a synergistic effect.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our observation clearly indicated that carvacrol and eugenol fumigation induced the activities of POD and PAL at a few points of incubation. The activities of POD and PAL in peaches exposed to the two EOs observed in this study were consistent with the previous report of Cindi et al (2016) and Liu et al (2016). CHI and b-1,3-glucase decompose chitin and b-1,3-glucan in the cell wall of pathogenic bacteria with a synergistic effect.…”
Section: Discussionsupporting
confidence: 93%
“…() and Liu et al . (). CHI and β‐1,3‐glucase decompose chitin and β‐1,3‐glucan in the cell wall of pathogenic bacteria with a synergistic effect.…”
Section: Discussionmentioning
confidence: 97%
“…Soluble solid content (SSC) was assessed in juices extracted from peaches and determined by a portable Brix meter (PAL‐1, Atago Co. Ltd, Tokyo, Japan). Titratable acid (TA) and ascorbic acid was measured by the method of Liu et al () and expressed as mg/g.…”
Section: Methodsmentioning
confidence: 99%
“…However, sodium o-phenylphenate is of limited use due to its risk of injuring fruit (Ismail & Zhang, 2004;Liu et al, 2009;Smilanick, Mansour, Margosan, Gabler, & Goodwine, 2005). In general, the demand for new antifungal compounds is of the utmost urgency, with a clear preference for identifying the promising natural products with antifungal activity (Liu et al, 2016).…”
mentioning
confidence: 99%